Organic Farming for Healthy Food Production and Land Sustainability for Supporting a Smart Agriculture in Indonesia: English - Hardaningsih, Wiwik; Budianta, Dedik; Madjid, Abdul; Aisyah; Syazili, As'ad (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Recently, people have suffered from many serious illnesses, such as kidney, cancer, osteoporosis, etc. One of the triggers is that the food eaten by human is not free from heavy metals. These heavy metals enter through the food chain during the crop cultivation. These heavy metals can come from artificial agrochemical inputs (such as synthesis P fertilizers and pesticides). One way to avoid the entry of heavy metals into plant is by implementing organic farming. Organic farming is an agricultural system that does not use synthetic chemical. The implication of organic farming are (1) maximizing the use local resources, (2) minimizing the use of chemical inputs, (3) ensuring biological functions, (4) maintaining a diversity of plant and animal species, (5) creating an attractive overall landscape that provides satisfaction for local communities, and (6) increasing the intensity of plants and animals in the form of polyculture, agroforestry, crop/animal systems integrated livestock etc. If organic farming principles are followed consistently then the food produced will be healthy and safe for humans and animals and save for land sustainability to support smart farming. Another benefit of organic farming is that natural resources will be sustainable and the environment will be protected from pollution and damage. To convince the Indonesian and global community, the organic products produced must be certified independently, the basis of which is SNI 6729-2016.